Cost Minimization Model of Gas Transmission Line for Indonesian SIJ Pipeline Network - Septoratno Siregar; Edy Soewono; Daniel Siregar; Satya A. Putra; Yana Budicakrayana (Institute for Research and Community Services, Institut Teknologi Bandung, 2003)
Optimization of Indonesian SIJ gas pipeline network is being discussed here. Optimum pipe diameters together with the corresponding pressure distribution are obtained from minimization of total cost function consisting of investment and operating costs and subjects to some physical (Panhandle A and Panhandle B equations) constraints. Iteration technique based on Generalized Steepest-Descent and fourth order Runge-Kutta method are used here. The resulting diameters from this continuous optimization are then rounded to the closest available discrete sizes. We have also calculated toll fee along each segment and safety factor of the network by determining the pipe wall thickness, using ANSI B31.8 standard. Sensitivity analysis of toll fee for variation of flow rates is shown here. The result will gives the diameter and compressor size and compressor location that feasible to use for the SIJ pipeline project. The Result also indicates that the east route cost relatively less expensive than the west cost.